Detection of a novel 16.3 variant allele at locus DYS533 in R1b males inhabiting southern South America: A 19-nucleotide insertion explains its origin based on Sanger sequencing results. (January 2023) - Sala, Andrea; Marino, Miguel; Guinudinik, Alejandra; Marcucci, Valeria; Cano, Hortensia; Rey, Silvia Vannelli; Bobillo, Cecilia; Castagnola, Josefina; Garrigós-Calivares, Lucía; Ginart, Santiago; Caputo, Mariela; Corach, Daniel
Abstract: We typed 1541 Y-STR haplotypes from reference samples along forensic casework investigations. In three haplotypes, we detected a variant allele designed as 16.3 at locus DYS533. This was confirmed by amplification using two commercial kits. Sanger sequencing revealing a novel motif corresponding to [TATC]12 repeats with a 19-bp insertion in the flanking upstream region. We propose its origin as an insertion at − 9.1 upstream of the repeat motifs. We searched other local databases and found this allele in various geographical areas of Argentina and neighbouring countries. The haplotypes share a common core of 10 Y-STRs (DYS389-I/13; DYS389-II/30; DYS19/14; DYS481/22; DYS438/12; DYS437/16; DYS635/23; DYS392/13; DYS393/13; GATA H4/11) and belong to the R1b haplogroup. This 16.3 allele is restricted to southern South America, which allows us to propose a local and relatively recent origin. The sequence described herein constitutes a novelty that could be considered in future criteria for the nomenclature of STRs based on massively parallel sequencing. Highlights: Novel sequence structure at locus DYS533. Upstream insertion explains a new variant allele DYS533/16.3. New variant allele associated to south american Y haplotypes.